Biocompatibility evaluation of lithium-hydroxyapatite composites - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2006)
Fifteen different lithium-hydroxyapatite composites were tested in this work. LiHA were prepared using 0.25 %, 1 % and 2 % of lithium and five different sintering temperature 900, 1000, 1100, 1200 and 1300 degrees C. Primary culture of osteoblasts were used to evaluate the biocompatibility of the samples, concerning to cell viability and alkaline phosphatase production. The 1% LiHA samples sintered at 1100, 1200 and 1300 degrees C showed the best results.
Keywords: lithium; hydroxyapatite; osteoblast; biocompatibility